Green tea leaf extract reduces viability and migration of cholesteatoma fibroblast of chronic suppurative otitis media cultured in vitro - Rizki, Anika; Suciati, Yulia; Hadi, Restu Syamsul (MEDISAINS, 2023)
Background: Chronic Suppurative Otitis Media (CSOM) is still a health problem, especially in developing countries. CSOM with cholesteatoma is a dangerous type. Cholesteatoma in CSOM sufferers can cause various complications. Therefore, alternative therapies are needed, such as green tea leaf extract. Green tea leaf extract can be an antioxidant and anti-inflammatory, but its effectiveness in treating CSOM has not been studied before, so research is needed..   Purpose: This research aimed to determine the effect of green tea leaf extract that could reduce viability and migration in cholesteatoma fibroblast of CSOM.Methods: This research was an in vitro experiment with a post-test-only control group design. The sample for this research was cholesteatoma fibroblast cells obtained from the isolation of patients with CSOM. The method used is Hoechst staining for viability and scratch techniques for cell migration with eight groups of cholesteatoma fibroblasts consisting of a negative control group (DMEM+FBS), DMEM group, two positive control groups dexamethasone (10 µM and 100 µM), and four green tea leaf extract group (10 µg/ml, 40 µg/ml, 80 µg/ml, and 160 µg/ml). Data analysis used One-Way ANOVA and Kruskal Wallis tests.Results: The results showed that the highest average cell viability was in the negative control group (165.33), and the lowest was in green tea leaf extract at a dose of 160 µg/ml (70.88). Cell migration at 72 hours showed that in the negative control group, there was faster closure of the scratch area (97,78%) and the slowest closure on green tea leaf extract at a dose of 160 µg/ml (13,81%).Conclusion: Green tea leaf extract can reduce the viability and migration in cholesteatoma fibroblast of CSOM. It shows the potential of green tea extract as an alternative to prevent cholesteatoma.